Analysing the Influence of Celebrities on Impulsive Buying Intention through Livestreaming: The Moderating Role of Financial Promotion in Online Commerce - Huu, De Dinh (Theoretical and Practical Research in Economic Fields; Vol 17 No 1 (2026): TPREF Volume XVII Issue 1(37) March 2026, 2026)
This study explores the impact of environmental factors in e-commerce livestreaming, including perceived expertise, trustworthiness, attractiveness, and parasocial interaction, on emotional arousal, trust, and consumers’ impulsive buying intention. Data collected from 433 consumers and analyzed using SPSS and SmartPLS reveal a key finding of the research, the strong moderating role of financial promotion, which significantly enhances the influence of emotional arousal and trust on impulsive buying intention in celebrity-hosted livestream settings. Moreover, a novel theoretical contribution is provided by testing the moderating role of financial promotion within the SOR framework, thereby extending the traditional SOR approach that has paid limited attention to the moderating effects of financial contextual factors in live shopping environments. These findings not only broaden the theoretical framework of online consumer behavior but also challenge the conventional assumption that emotions predominantly drive impulsive buying behavior.